Integrated and distributed manufacturing, a multi-agent perspective - Barata, José (2010)
There has been a large and rapid evolution in terns of the paradigms and technologies to support the development of distributed manufacturing systems and real-time applications. This paper starts with a survey of the main proposals in the area based on the experience gained by the authors in various fields pertaining to manufacturing device modelling, control and supervision, industrial messaging, production management and reengineering methodology. The rational for a multi-agent approach is discussed as the available technologies to support the development of agent-based applications are summarised. Finally an implementation of controlling agents in a flexible manufacturing system is described and discussed.